PJMHS 2021
DOI: 10.53350/pjmhs211582157
|View full text |Cite
|
Sign up to set email alerts
|

Compare the Outcome of Percutaneous Aspiration with Incisional Drainage for Management of Breast Abscess

Abstract: Objective: To compare the outcome of percutaneous aspiration with incision drainage for management of breast abscess. Study Design: Comparative study Place and Duration of Study: Department of Surgery Unit-1, Sandeman Provincial Hospital Quetta from 1st October 2020 to 31st March 2021. Methodology: One hundred and ten women age aged between 18-65 years of age were enrolled. Patients details demographics age, weight, height and body mass index were recorded after taking informed written consent. Women had breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Breast abscesses are one of the most prevalent causes of morbidity in women. Due to improvements in maternal cleanliness, nutrition, and standard of living, breast abscesses are less prevalent in wealthy nations, but they continue to be a significant concern for nursing women in developing nations 6 . A study reported that the age range of patients who found that breast abscesses are most prevalent among women aged 18 to 50 years 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Breast abscesses are one of the most prevalent causes of morbidity in women. Due to improvements in maternal cleanliness, nutrition, and standard of living, breast abscesses are less prevalent in wealthy nations, but they continue to be a significant concern for nursing women in developing nations 6 . A study reported that the age range of patients who found that breast abscesses are most prevalent among women aged 18 to 50 years 3 .…”
Section: Discussionmentioning
confidence: 99%